1998
DOI: 10.1093/jac/42.1.107
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous-to-oral switch guidelines on the use of parenteral antimicrobials in medical wards

Abstract: The effect of an intravenous (i.v.)-to-oral switch policy on antibiotic prescribing in general medical wards was examined. Three audits, each of 2 months' duration, were carried out to examine the duration of i.v. therapy and length of patient stay. The first audit (S1) was performed before the introduction of switch guidelines, the second (S2) after guidelines had been placed in patient case-notes and the third (S3) after the guidelines had been introduced into the drug charts. The duration of i.v. therapy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 0 publications
5
43
1
5
Order By: Relevance
“…This study included a control and intervention group in both phases, following recommendations from Ramsay et al [14]. This contrasts with other published studies, which used an uncontrolled before and after design, with no control group included in the post-intervention phase of the study [4][5][6][7][8][9][10][11][12][13]. The methodology used in this study continues to demonstrate the utility of a systematic plan for switching to PO antimicrobials, as recommended by the IDSA [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study included a control and intervention group in both phases, following recommendations from Ramsay et al [14]. This contrasts with other published studies, which used an uncontrolled before and after design, with no control group included in the post-intervention phase of the study [4][5][6][7][8][9][10][11][12][13]. The methodology used in this study continues to demonstrate the utility of a systematic plan for switching to PO antimicrobials, as recommended by the IDSA [2].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, nursing time spent preparing IV doses is reduced and patient comfort and mobility is improved [3]. Initiatives to promote sequential therapy have also been shown to reduce the duration of IV treatment and hospital stay with resulting cost savings [4][5][6][7][8][9][10][11][12][13]. For these reasons, 'antimicrobial switch strategy' criteria and guidelines were implemented in a 753 bed university hospital in Dublin, Ireland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequential therapy is defined as conversion from intravenous to oral formulation of the same medication while maintaining equivalent potency [2]. Several advantages have been associated with this strategy: less preparation time, easier drug administration, patient comfort, lower risk of bacteraemia and thrombophlebitis, savings in antibiotic costs and potential shortening of the length of hospital stay [2][3][4][5][6][7][8][9][10][11][12][13][14]. Several clinical trials have demonstrated the efficacy of sequential therapy [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizar la vía oral desde el principio es posible con algunos fármacos con excelente biobisponibilidad como clindamicina, metronidazol o fluoroquinolonas (2,14,19,20).…”
Section: Discussionunclassified